CD11c-Cre driven deletion of Irf8 reveals the effect of somatic mosaicism in a mouse model of SLE - Wang, Hongsheng; Qi, Chen-Feng; Scott, Bethany; Kole, Hemanta; Bolland, Silvia (Frontiers in Immunology, 2026)
The pathogenesis of systemic lupus erythematosus (SLE) is caused by a complex mix of genetic factors that lead to dysregulation of the immune response. Mild susceptibility or resistance factors can tilt the scale towards or against pathology. Here, we present evidence for the Irf8 gene as a lupus protective factor in conditions of haploinsufficiency or mosaicism. We targeted Irf8 expression in mice deficient in Fcgr2b, a well characterized mouse model of SLE. As is the case in human SLE, hyperresponsive B cells and dendritic cells (DCs) are causal factors at various stages of disease in Fcgr2b-deficient mice (R2-/-). Since Irf8 is essential for the generation of cDC1s, we used conditional deletion with various known DC-targeting Cre systems to delete Irf8. All conditional systems tested to delete Irf8 reduced the titer of antinuclear antibodies and abrogated kidney pathology in R2-/- mice. In addition to the expected effect of Irf8 deletion in cDC1s, we unexpectedly found that mosaic deletion of Irf8 also occurred in B cells and other immune cells. Using mixed bone marrow chimeras we determined that the aborted disease in Irf8f/fCD11c-Cre+R2-/- and Irf8f/fItgax-Cre+R2-/- mice could be attributed to the inability of B cells with partial reduction of IRF8 to produce autoantibodies. Therefore, these results reveal IRF8 as a susceptibility factor of SLE even in cases of mild changes of expression levels and mosaic somatic deletion of the gene in B cells.